Parental Use of Internet to Navigate Online Health Information for Their Children: An Indonesian Context - Hesty Utami Ramadaniati; Nurita Andayani; Zata Yumni Azizah (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2021)
Internet-resourced health information becomes increasingly common amongst parents before doctor consultation. This study aimed to explore the demographics of online health information-seeking parents and the type of information on children’s healthcare needs and the relationship between the demographics and the online sources. A cross-sectional study was conducted at two Primary Health Centers (PHC) in Jakarta. The respondents were parents of acutely ill children seeking online health information before visiting PHC. A validated questionnaire was distributed to the respondents. Parents’ demographics and type of information were analyzed descriptively. The relationship between the demographics and the information source was tested using the Chi-Square test. 478 respondents were participating in this study where most of the respondents were mothers (75.1%), aged 26-35 years (57.7%), and had 1-2 children (70.7%). Most of them were high-school graduates (64.9%) and unemployed (49.6%). Google (61.5%) was predominantly the most frequently used digital media, followed by websites run by doctors (21.9%). The most sought information included illness causes, transmission probability, treatment, and medicines’ side effects. There was no significant relationship between any demographics and the types of online sources. In conclusion, illness-related basic information is used by most parents to be informed before seeing doctors. The link between parents’ characteristics and the selection of digital media could not be determined.